Religijna terminologia Jeznika z Kolb w dziele „Przeciwko sektom”. Wybrane zagadnienia - Magakian, Grair (Vox Patrum, 2025)
The article analyzes the issue of theological terminology in the treatise by Yeznik of Kolb Against the Sects, focusing on the etymology of key concepts and their significance in shaping early Christian thought in Armenia. The structure of the analysis includes a discussion of the historical context of the work, the division of the treatise into four parts, and a detailed presentation of selected terms. The author examines their sources, semantic range, and function in the polemics against dualistic and pagan religious systems. The methodology is based on source analysis, etymology, and theology, considering Greek, Syrian, and Iranian influences. The main conclusion is that Yeznik created a new layer of terminology, adapting philosophical concepts to the Christian doctrine of monotheism. Ancient sources include the writings of the Church Fathers and the Bible, which Yeznik adapted for the needs of Armenian theology. The contribution of this work lies in demonstrating Yeznik’s role as a pioneer of Armenian theological terminology and its significance for the further development of Christian thought in Armenia. The article makes an important contribution to the study of the language and theology of ancient Christianity.